Intelligent Digital Learning Services Laboratory in Smart Classroom Environment - et. al., Yasdinul Huda, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The application of the concept of the Internet of Things in a laboratory environment will improve the quality of learning processes in the classroom because several activities are represented by technology so that lecturers and students will organize their assignments more efficiently and effectively. This paper is designed to describe the concept of models, symbols, technology, and the Internet of Thing’s challenges for a better life. The Internet of Things' role illustrates the broader concept of Smart Classroom by offering the integration of multiple ThingSpeak sensors, microcontrollers, actuators, and equipment as the Internet of Things applications and APIs in authenticating experienced and prepared smart laboratory models. The smart laboratory system modeling results based on the Internet of Things are expected to support digital learning services, automatic data processing, and collect statistics on students' whereabouts in each practicum course.